Effect of thickener and reservoir parameters on the filtration property of CO2 fracturing fluid. Issue 14 (17th July 2020) - Li, Qiang; Wang, Yanling; Wang, Fuling; Wu, Jiangping; Usman Tahir, Muhammad; Li, Qingchao; Yuan, Lin; Liu, Zhonghua
ABSTRACT: Some drawbacks of the hydraulic fracturing technology included the water pollution and reservoir destruction, hindered its development and application in shale reservoirs. CO2 fracturing fluid is considered to be an excellent substitution to conduct the fracturing operation because of its cheapest, enhance gas production and environment friendly. However, the low viscosity and high filtration property of pure CO2 are viewed as a huge challenge to develop CO2 fracturing technology. In this paper, we synthesize a modified silicone as a CO2 thickener to investigate the effect of different thickener parameters, temperature, and pressure on the CO2 filtration property in low permeability reservoirs. This is a working theory which is based on the organic synthesis and unconventional oil and gas exploration. We carry out several studies which have demonstrated that the CO2 filtration coefficient deceased as an increase of CO2 thickener and carbonyl group content, molecular weight, and pressure. When the temperature rises, an increasing filtration coefficient of liquid CO2 was presented. Physical parameters of thickener display a significant impact on CO2 filtration coefficient. A thickener with a reasonable chemical structure significantly was not only improving the CO2 viscosity but also the filtration coefficient has. It was also found that fracturing fluid viscosity is the ultimate factor that changes the CO2 filtration property.